ChemInform Abstract: Synthesis and Characterization of the Ternary Telluroargentate K4[Ag18Te11]. Issue 4 (January 2015) - Davaasuren, Bambar; Dashjav, Enkhtsetseg; Rothenberger, Alexander
Abstract The title compound is solvothermally synthesized from a mixture of Ag(OAc), K2Te, and elemental Te in en (autoclave, 160 °C, 5 d, 30% yield).